Stock assessment of pomfrets off west coast of India - Khan, Mohammad Zafar; Kumaran, M; Jayaprakash, A A; Scariah, K S; Deshmukh, V M; Dhulkhed, M H (Indian Journal of Fisheries, 2011)
Pomfrets contribute 36 501 tonnes to the annual marine fish landings in India. Pampus argenteus andFannia niger are the prime SpeCIes forming 65.0% and 34.0% respectively of the pomfret catch. Gujarat andMaharashtra share 42.6% and 35.9% of P. argenteus and 33.3% and 22.8% of F. niger exploited, respectively.The growth parameters for P. argenteu.f offMaharashtra and Kamataka and MSY off Maharashtra (9 551tonnes) and Kamataka (374 tonnes) were estimated. The results indicated high fishing pressure to the extent of40% off Kamataka. Large-scale destruction of young ones by dol nets at Bessein (Maharashtra) resulted inrecruitment overfishing as the catches came down to 565 tonnes (1991) from 5 612 tonnes (1984).The growth parameters for F niger for Kerala and Kamataka were estimated. MSYestimates were 1 055tonnes off Kerala and 1856 tonnes off Kamataka. The effort needs to be reduced by 60% off Kamataka